Improvement of vertical organic field-effect transistors by surface modification of metallic source electrodes. (13th October 2017) - Chang, Jui-Fen; Lai, Yi-Chien; Yang, Rui-Hao; Yang, Yaw-Wen; Wang, Chia-Hsin
Abstract: A proper design of the injection barrier between a source electrode and an active layer is essential to achieve high-performance vertical organic field-effect transistors (VOFETs). Here, we show that a modification of metallic source electrodes with thiol-based self-assembled monolayers (SAMs) is effective in controlling the electrode work function and injection barrier into the active layer, leading to a significantly reduced off-current and undegraded on-current in an optimized VOFET. For the studied C60 VOFETs with Ag electrodes, the on/off ratio improves from <10 to 10 3 –10 4 when the injection barrier is varied from 0.02 to 0.33 eV by SAM modification.